Antiseizure and antifriction characteristics of Al-Si-Pb alloys - Pathak J.P.; Torabian H.; Tiwari S.N. (My University, 2025)
The antiseizure and antifriction characteristics of a number of Al-Si-Pb alloys with silicon contents in the range 2-20 wt.% and lead contents in the range 0-10 wt.% were investigated under different lubrication conditions using a bearing test machine. With continuous oil lubrication, bearings made of eutectic and hypereutectic base alloys run without seizure up to the regimes of boundary and mixed lubrication, whereas bearings made of hypoeutectic base alloys seize under conditions in which the above alloys are under hydrodynamic lubrication. The addition of lead to aluminium-silicon alloys is generally found to reduce interfacial friction and improve their ability to resist seizure. A lower friction coefficient and a higher seizure load are obtained for Al-Si-Pb alloys bearing in semi-dry sliding conditions compared with those observed for dry conditions. © 1997 Elsevier Science S.A. All rights reserved.